Dermatology today and tomorrow: from symptom control to targeted therapy. (18th December 2018) - Blume‐Peytavi, U.; Bagot, M.; Tennstedt, D.; Saint Aroman, M.; Stockfleth, E.; Zlotogorski, A.; Mengeaud, V.; Schmitt, A.M.; Paul, C.; Lim, H.W.; Georgescu, V.; Dréno, B.; et al.
Abstract: For many decades and until recently, medical approach to dermatologic diseases has been based on the physician's ability to recognize and treat symptoms. Nowadays, advances in the understanding of the biology of diseases and in technologies for intervening against them have allowed physicians to diagnose and treat underlying disease processes rather than simply addressing the symptoms. This means that rather than addressing 'the disease in humans', physicians can now address the particular pathologic (biologic, molecular) disturbance as it presents in the individual patient, i.e., physicians now can practice something much closer to 'personalized medicine', leading to greater benefits for the patients and the health of society in general. The deeper understanding of ultraviolet radiation, the importance of photoprotection and increased knowledge about signalling pathways of melanoma and carcinoma have led to more complete care for the dermatologic patient. The current popularity for excessive exposure to the sun, without adequate application of the appropriate photoprotection remedies, is the origin of melanoma, but also for the weakening of the structure and functions of the skin. Indeed, fragility of the skin can affect humans around the world. In the senior population, this skin fragility is accompanied by pruritus, whereas atopic dermatitis is an inflammatory disease with highest prevalence in children and adolescents. Acne, the number one reason for dermatologic consultations worldwide, increases its prevalence in adolescents and in females. Senescent alopecia affects humans after menopause and andropause. The articles in this publication present an overview of the current advanced understanding of the diagnosis and therapeutic approaches in 6 fields of dermatology – dermatopaediatry and gerontodermatology, oncodermatology, hair loss, atopic dermatitis, photoprotection and acne – and thereby serve as a useful compendium of updated information and references for all healthcare professionals who see patients with presentations of the symptoms of these diseases.